Evaluation of Acceptance of Pre-School Child Nutrition Surveillance Application Prototype Using the TAM Model - Harwanto, Fatria (STIKES Yayasan RS.Dr.Soetomo, 2025)
Health and nutrition surveillance in preschool-aged children is essential for supporting optimal growth, and digital technologies like mobile applications can simplify monitoring dental health, nutrition, and immunization history. This study analyzed the acceptance of a prototype child health and nutrition surveillance app using the Technology Acceptance Model (TAM). The app was tested with 54 preschool students’ guardians, with data collected via a TAM-based questionnaire assessing perceived usefulness, perceived ease of use, attitude toward use, and intention to use the app. Results indicated that most guardians had positive perceptions of the app's usefulness and ease of use, which positively influenced their attitudes and intentions to use it for child health surveillance. The prototype was well-received and shows potential as an effective tool for preschool children's health monitoring, though further research on a larger scale is needed to validate these findings.